Knowledge and practice of women regarding cervical cancer in a primary health care unit - Leite, Maria Fernanda; De Vitta, Fabiana Cristina Frigieri; Carnaz, Letícia; De Conti, Marta Helena Souza; Marta, Sara Nader; Gatti, Márcia Aparecida Nuevo; Simeão, Sandra Fiorelli de Almeida Penteado; De Vitta, Alberto (Faculdade de Filosofia e Ciências, 2014)
Objectives: evaluating the level of information about the examination of uterine cervical cancer and its association with sociodemographic variables in women of a health care unit in the city of Bauru, São Paulo, Brazil. Methods: we conducted a cross-sectional descriptive study with 370 women aged 25 to 59, through structured interviews in their own homes; we used descriptive statistics and the χ2 test. Results: 40.5% of the women had not undergone the Papanicolaou test at the recommended frequency; 58.2% incorrectly defined the test, and 69.5% did not know about the risk factors for the development of cervical cancer; the knowledge about the test showed statistically significant association with schooling and family income of the studied population. Conclusions: women present deficiencies on the proper practice of the Papanicolaou test, on knowledge about the test, risk factors and prevention methods. Therefore, it is necessary to develop primary health actions for the most vulnerable population.
Keywords: Knowledge; Risk factors; Uterine cervical neoplasms; Vaginal wet mount; Women's health